Work Motivation Is Not Generational but Depends on Age and Period - Martin Schröder (Journal of Business and Psychology, 2023)
Many argue that work motivation varies with year of birth, suggesting the utility of generational labels such as Z, Y, X, or Baby Boomer. This article tests this generational hypothesis by using multilevel regressions with data from 584,217 individuals sampled by the Integrated Values Survey in 113 countries over more than 30 years. The results show that the importance of work first increases and then decreases with an individual's age and that the importance of work tends to decrease for everyone with the passing of historical time. These age and period effects make later-born generations seem work averse, while birth year and thus generational membership hardly explain work motivation after accounting for age and period effects. The article also tests whether ten other work-related attitudes can be explained through generational membership. The results suggest that the historical time period and an individual's life course explain work motivation and work attitudes better than generational membership. This life course and historical explanation is suggested as an alternative to the generational hypothesis of work motivation and attitudes that prevails in much of the literature.
Keywords: 650; APC analysis; Generation Z; Generation Y; Generation X; Babyboomer; Attitude change; Work motivation; Life course; Karl Mannheim